2019
DOI: 10.1186/s40635-019-0270-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased mortality in elderly patients with acute respiratory distress syndrome is not explained by host response

Abstract: BackgroundAdvanced age is associated with increased mortality in acute respiratory distress syndrome (ARDS) patients. Preclinical studies suggest that the host response to an injurious challenge is age-dependent. In ARDS patients, we investigated whether the association between age and mortality is mediated through age-related differences in the host response.MethodsThis was a prospective longitudinal observational cohort study, performed in the ICUs of two university-affiliated hospitals. The systemic host re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 67 publications
(63 reference statements)
1
14
0
Order By: Relevance
“…The start of ARDS heralds a marked increase in mortality up to 50%. (36) It is comparable to the mortality of 43% from ARDS from other causes in the elderly patients (over 67 years) (37) and may reflect the older age predominance of COVID-19 complications. The hallmarks of this phase are:…”
Section: Onset Of Ardsmentioning
confidence: 85%
“…The start of ARDS heralds a marked increase in mortality up to 50%. (36) It is comparable to the mortality of 43% from ARDS from other causes in the elderly patients (over 67 years) (37) and may reflect the older age predominance of COVID-19 complications. The hallmarks of this phase are:…”
Section: Onset Of Ardsmentioning
confidence: 85%
“…Other investigators have reported no significant difference in mortality using a dichotomous age cut-off of 65 years, potentially supporting the notion that the relationship between age and ARDS may be more complex (44). While age is associated with ARDS mortality, there is no significant difference between ventilator or ICU free days, length of stay in ICU or length of stay in hospital between patients above 65 and those under 65 (12,45). Indeed, a number of studies have concluded that comorbidities rather than age primarily affect prognosis following ICU admission (46)(47)(48).…”
Section: Clinical Characteristics Of Aging In Ardsmentioning
confidence: 92%
“…However, to date, no single specific ARDS biomarker has been validated (83). Analysis of systemic inflammatory mediators and endothelial activation markers in plasma from adults with ARDS found that, compared to younger patients, elderly patients had lower levels of inflammatory mediators and endothelial activation markers (interleukin (IL)-6, IL-8, IL-10, interferon-γ, fractalkine, intracellular adhesion molecule (ICAM)-1, E-selectin) and higher levels of platelet factor-4 and tissue plasminogen activator (tPA) (12). Furthermore, advanced age was found to be independently associated with increased plasma levels of tPA and decreased plasma levels of fractalkine and E-selectin (12).…”
Section: Impact Of Age On Treatment Strategies and Specific Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma ANG II level is increased in patients infected with H7N9 and H5N1, followed by a decrease in ACE2 activity, with no change in ACE activity ( 21 , 84 ). Further, ACE activity increased and ACE2 decreased in the bronchoalveolar lavage fluid of animals and patients with acute respiratory distress syndrome (ARDS) ( 52 , 70 , 71 ). Thus, it can be hypothesized that, with a decrease in ACE2 followed by SARS-CoV-2 infection, ANG II would increase.…”
Section: Angiotensin II and Coronavirus Infection: Is There A Causal mentioning
confidence: 99%